Animal models in the study of diabetic erectile dysfunction: mechanisms and applications - Zhang, Xin; Chen, Yihao; Qian, Jiahua; Si, Yuhe; Wang, Chenxi; Wang, Jingwei; He, Qiang; Ma, Jianxiong (Frontiers in Endocrinology, 2025)
BackgroundDiabetic erectile dysfunction (DMED) is a common complication of diabetes. While research on DMED relies primarily on animal models, replicating the intricate etiology and multi-system interactions of human DMED in a single model remains a challenge.AimThis article provides a comprehensive overview of animal models used in DMED research and emphasizes the crucial role they play in understanding the pathogenesis and treatment of DMED.MethodsA comprehensive medical literature was searched in PubMed and Medline, focusing on original studies and systematic reviews of original studies involving animal models of diabetic erectile dysfunction. Clinical studies, editorials, letters, reviews, and non-English articles were excluded.ResultsThis article compiles various animal models currently used in the study of diabetes and diabetic erectile dysfunction (DMED), with a particular emphasis on the application of rodent models such as rats and mice. These animals demonstrate significant advantages in terms of economy, practicality, and reproducibility in DMED research and share similarities with humans in tissue morphology and functional characteristics.ConclusionThis manuscript offers researchers multiple insights into selecting animal models for DMED, particularly considering their practicality, cost-effectiveness, and reproducibility. The integrated information serves as a valuable reference for researchers in choosing suitable models.